The noradrenergic paradox: implications in the management of depression and anxiety - Montoya A; Bruins R; Katzman M; Blier P (Neuropsychiatric Disease and Treatment, 2016)
Alonso Montoya,1 Robert Bruins,1 Martin A Katzman,2 Pierre Blier3 1Eli Lilly Canada Inc, 2START Clinic for the Mood and Anxiety Disorders, Toronto, 3Mood Disorders Research Unit, Institute of Mental Health Research, University of Ottawa, Ottawa, ON, Canada Abstract: Both major depressive disorder and the anxiety disorders are major causes of disability and markedly contribute to a significant global burden of the disease worldwide. In part because of the significant socioeconomic burden associated with these disorders, theories have been developed to specifically build clinical treatment approaches. One such theory, the monoaminergic hypothesis, has led to the development of several generations of selective and nonselective inhibitors of transporters of serotonin and norepinephrine, with the goal of augmenting monoaminergic transmission. These efforts have led to considerable success in the development of antidepressant therapeutics. However, there is a strong correlation between enhanced noradrenergic activity and fear and anxiety. Consequently, some physicians have expressed concerns that the same enhanced noradrenergic activity that alleviates depression could also promote anxiety. The fact that the serotonergic and noradrenergic reuptake inhibitors are successfully used in the treatment of anxiety and panic disorders seems paradoxical. This review was undertaken to determine if any clinical evidence exists to show that serotonergic and noradrenergic reuptake inhibitors can cause anxiety. The PubMed, EMBASE, and Cochrane Library databases were searched, and the results limited to randomized, double-blind, placebo-controlled studies performed in nongeriatric adults and with clear outcome measures were reported. Based on these criteria, a total of 52 studies were examined. Patients in these studies suffered from depression or anxiety disorders (generalized and social anxiety disorders, panic disorder, and posttraumatic stress disorder). The large majority of these studies employed venlafaxine or duloxetine, and the remainder used tricyclic antidepressants, atomoxetine, or reboxetine. All the studies reported clinically significant alleviation of depressive and/or anxious symptoms by these therapeutics. In none of these studies was anxiety a treatment-emergent adverse effect. This review argues against the impression that enhanced generalized noradrenergic activity promotes the emergence of anxiety. Keywords: anxiety, atomoxetine, desvenlafaxine, duloxetine, monoamine, norepinephrine reuptake inhibitor, norepinephrine transporter